Clinical characteristics and treatment outcome of oropharyngeal squamous cell carcinoma in an endemic betel quid region - Chen, Tseng-Cheng; Wu, Chen-Tu; Ko, Jenq-Yuh; Yang, Tsung-Lin; Lou, Pei-Jen; Wang, Cheng-Ping; Chang, Yih-Leong (Scientific reports, 2020)
The clinical characteristics of oropharyngeal squamous cell carcinoma (OPSCC) may be different between endemic and non-endemic regions of betel nut chewing. The impact of combined alcohol drinking/betel quid chewing/cigarette smoking (ABC) exposure on the survival of OPSCC remains unclear. We reviewed the medical records of OPSCC patients between 1999 and 2013. Immunohistochemical staining of p16 and HPV genotype detection by DNA Polymerase chain reaction were both performed for each tumor. A total of 300 eligible patients including 74 HPV+ OPSCC patients and 226 HPV− OPSCC patients were enrolled. The 5-year disease-free survival rates for the HPV−, HPV+ OPSCC with and without ABC patients were 49.8%, 58.4% and 94%, respectively. The 5-year overall survival rates for the patients with HPV−, HPV+ OPSCC with and without ABC patients were 46%, 57.4% and 86%, respectively. Advanced locoregionally disease (T3/T4, N2/N3), HPV- OPSCC, combined 2 or all ABC exposure were the independent adverse prognostic factors for disease-free and overall survival. Therefore, our data suggest that in an endemic region of betel quid chewing, HPV− OPSCC comprises the majority of OPSCC and has a worse survival. Combined 2 or all ABC exposure had a significant negative impact on disease-free and overall survival.